Analisis Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus, dan Dana Keistimewaan terhadap Kemiskinan di Provinsi Daerah Istimewa Yogyakarta - Rizki Lutfiana Saputri; Sodik Dwi Purnomo; Bagus Adhitya (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of Local Own Revenue (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), and Privilege Funds (DAIS) on poverty rates across regencies/cities in the Special Region of Yogyakarta (DIY) from 2013 to 2024. A descriptive quantitative approach utilizing panel data regression analysis was employed. Partially, Local Own Revenue (PAD) has a negative and significant effect on poverty rates. Conversely, General Allocation Funds (DAU), Special Allocation Funds (DAK), and Privilege Funds (DAIS) do not exert a significant effect on poverty rates. The implications of this study emphasize the necessity of optimizing regional fiscal independence through PAD, alongside reorienting and enhancing the allocation efficiency of central transfer and privilege funds to align them directly with targeted poverty alleviation programs.